2000
DOI: 10.1152/ajprenal.2000.278.3.f375
|View full text |Cite
|
Sign up to set email alerts
|

Role of Na+/H+exchanger NHE3 in nephron function: micropuncture studies with S3226, an inhibitor of NHE3

Abstract: Na(+)/H(+) exchanger NHE3 is expressed in the luminal membrane of proximal tubule and thin and thick ascending limb of Henle's loop. To further define its role, the novel NHE3 inhibitor S3226 was employed in micropuncture experiments in nephrons with superficial glomeruli of anesthetized rats. Microperfusion of proximal convoluted tubule with S3226 revealed a dose-dependent inhibition of reabsorption (IC(50) of 4-5 microM) with a maximum inhibition of 30% for fluid and Na(+). During microperfusion of Henle's l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
1
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 22 publications
4
75
1
3
Order By: Relevance
“…Studies using isolated brush border vesicles and perfused tubules are consistent with the concept that a major fraction of NaCl entry across the apical membrane of proximal tubule cells occurs via Cl Ϫ -formate exchange in parallel with Na ϩ -H ϩ exchange and H ϩ -coupled recycling of formate (2)(3)(4)(5)(6)(7). Whereas several lines of evidence indicate that the transporter primarily responsible for apical Na ϩ -H ϩ exchange in the proximal tubule is NHE3 (8)(9)(10)(11)(12)(13), the transporter responsible for apical Cl Ϫ -formate exchange has yet to be identified.…”
supporting
confidence: 65%
“…Studies using isolated brush border vesicles and perfused tubules are consistent with the concept that a major fraction of NaCl entry across the apical membrane of proximal tubule cells occurs via Cl Ϫ -formate exchange in parallel with Na ϩ -H ϩ exchange and H ϩ -coupled recycling of formate (2)(3)(4)(5)(6)(7). Whereas several lines of evidence indicate that the transporter primarily responsible for apical Na ϩ -H ϩ exchange in the proximal tubule is NHE3 (8)(9)(10)(11)(12)(13), the transporter responsible for apical Cl Ϫ -formate exchange has yet to be identified.…”
supporting
confidence: 65%
“…The present results are consistent with the absence of NHE3 from mouse CCD, because no mRNA was demonstrated by RT-PCR, although the primers used in the study were able to detect NHE3 mRNA from whole mouse kidney. NHE3 is expressed in the apical membrane of the proximal convoluted tubule, where it appears to mediate a significant fraction of Na ϩ and water reabsorption (26). In the TAL, NHE3 is expressed in the apical membranes of both cortical and medullary segments; however, this isoform does not appear to contribute to salt reabsorption in the TAL under normal conditions (26), but its activity is increased by chronic metabolic acidosis (15).…”
Section: Discussionmentioning
confidence: 99%
“…NHE3 is expressed in the apical membrane of the proximal convoluted tubule, where it appears to mediate a significant fraction of Na ϩ and water reabsorption (26). In the TAL, NHE3 is expressed in the apical membranes of both cortical and medullary segments; however, this isoform does not appear to contribute to salt reabsorption in the TAL under normal conditions (26), but its activity is increased by chronic metabolic acidosis (15). A question arising from the present study is whether the profile of NHE mRNA expression that we have observed reflects functional protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-incubated experimental larvae were exposed to the following concentration of inhibitor (transporter/mechanism targeted is given in parentheses): 100 µmol l −1 bafilomycin (VA); 100 µmol l methazolamide (carbonic anhydrase, CA). Selection of the concentration for each inhibitor was based on previous invertebrate or vertebrate tissue studies (MacVicker et al, 1993;Marcaggi et al, 1999;Vallon et al, 2000;Weihrauch, 2006;Tsui et al, 2009;Nguyen and Donini, 2010;Del Duca et al, 2011). All the inhibitors contained 0.1% DMSO in 0.5 mmol l −1 NH 4 Cl, therefore control larvae were pre-incubated in 0.5 mmol l −1 NH 4 Cl containing 0.1% DMSO.…”
Section: Siet Techniquementioning
confidence: 99%